2020
DOI: 10.1016/j.tranon.2019.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltrating Lymphocytes and NHERF1 Impact on Prognosis of Breast Cancer Patients

Abstract: BACKGROUND: Breast cancer (BC) is a heterogeneous disease, and patients with apparently similar clinicopathological characteristics in clinical practice show different outcome. This study evaluated in primary BCs and in the subgroup of the triple-negative breast cancers (TNBCs) the level of tumor infiltrating lymphocytes (TILs), Na+/H+ exchanger regulatory factor 1 (NHERF1) expression, and their association respect to the clinical outcome of patients. MATERIAL AND METHODS: NHERF1 expression was assessed by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Immunotherapy, such as programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) inhibitors, plays a good anti-tumor effect in the treatment of malignant tumors, such as lung cancer ( Cheng et al, 2020 ; Eguren-Santamaria et al, 2020 ) and melanoma ( Cuevas and Daud, 2018 ; Albershardt et al, 2020 ). Moreover, increasing numbers of studies showed that tumor-infiltrating lymphocytes, such as tumor-associated macrophages (TAMs) and tumor-infiltrating neutrophils (TINs), were directly related to the patients’ prognosis and efficacy of immunotherapy ( Bocchialini et al, 2020 ; He et al, 2020 ; Schirosi et al, 2020 ; Stenzel et al, 2020 ). Therefore, the study of the interaction between tumor and immunity and identification of novel targets of immunotherapy are of great clinical significance for the treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy, such as programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) inhibitors, plays a good anti-tumor effect in the treatment of malignant tumors, such as lung cancer ( Cheng et al, 2020 ; Eguren-Santamaria et al, 2020 ) and melanoma ( Cuevas and Daud, 2018 ; Albershardt et al, 2020 ). Moreover, increasing numbers of studies showed that tumor-infiltrating lymphocytes, such as tumor-associated macrophages (TAMs) and tumor-infiltrating neutrophils (TINs), were directly related to the patients’ prognosis and efficacy of immunotherapy ( Bocchialini et al, 2020 ; He et al, 2020 ; Schirosi et al, 2020 ; Stenzel et al, 2020 ). Therefore, the study of the interaction between tumor and immunity and identification of novel targets of immunotherapy are of great clinical significance for the treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…TIL levels are higher in highly proliferating tumors, including human epidermal growth factor receptor 2 (HER2)-positive and TNBC (3). TILs have a strong prognostic and predictive significance, and high TIL levels are positively correlated with pathological complete response rate and patient survival rate (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Инфильтрация опухоли лимфоцитами, как показали ретроспективные исследования, связана с повышением показателей выживаемости у пациентов с различными злокачественными новообразованиями (ЗНО), такими как колоректальный рак, меланома, рак молочной железы (РМЖ) и НМРЛ [16][17][18][19]. Набольшее количество клинических исследований, изучавших прогностическую значимость опухоль-инфильтрирующих лимфоцитов (ОИЛ), было посвящено РМЖ [20,21]. Было установлено, что выраженная инфильтрация опухоли у больных РМЖ цитотоксическими CD8 + Т-клетками коррелировала с выживаемостью пациентов [22] и ответом на химиотерапию.…”
Section: опухоль-инфильтрирующие лимфоциты -биомаркеры эффективности терапии препаратами ингибиторов контрольных точекunclassified